ANALISIS KURVA PHILLIPS DI INDONESIA - Tanjung, Ahmad Albar; Annisa Anggreini Siswanto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This research aims to investigate whether the relationship between unemployment and inflation in Indonesia is by the Phillips curve theory. This research is quantitative. The estimation method used is ECM Two-Step Engle-Granger. in the long term, it is estimated using Ordinary Least Square (OLS), while in the short term it is estimated using the Error Correction Model (ECM). The cointegration test uses the Engle-Granger cointegration test. The data used are secondary level data, wage rate data as a proxy for inflation, and unemployment rates from 1991-2020 obtained from the world bank. The findings of this study are that in the short term, the unemployment rate is negatively related to inflation but is not significant, meaning that a trade-off between the unemployment rate and inflation occurs but the effect is not significant. In other words, in Indonesia, the relationship between the unemployment rate and inflation follows the Phillips Curve theory, but in the long run, there is a positive relationship between the unemployment rate and inflation but it is not significant.